Analisis Implementasi Good Governance Pada Pengelolaan Anggaran Pendapatan Dan Belanja Nagari - Gustiman Candra; Herlina Helmy; Nayang Helmayunita (Universitas Negeri Padang, 2019)
This research aims to find out how to manage the Nagari Revenue and Expenditure Budget (APBNagari) in Koto Nan Tigo Utara Surantih and Koto Nan Tigo Selatan Surantih, Sutera Subdistrict, Pesisir Selatan District and find out how good governance is implemented in the management of the Nagari Income and Expenditure Budget (APBNagari ) in Koto Nan Tigo Utara Surantih and Koto Nan Tigo Selatan Surantih, Sutera District, Pesisir Selatan District. To achieve these objectives, qualitative research methods are used. Data collection techniques are carried out by interview, observation and documentation. The results of the study showed: (1) Management of APB Nagari in Koto Nan Tigo Utara Surantih and Koto Nan Tigo Selatan Surantih based on Permendagri Number 20 of 2018 concerning Village Financial Management there were problems at the planning stage. Nagari Koto Nan Tigo Selatan Surantih late in the Determination of RPJM Nagari and APB Nagari and Nagari Koto Nan Tigo Utara Surantih was only late in the APB Nagari determination. The late stipulation of the APB Nagari was due to the issuance of regulations from the regency to the Nagari. The stages of administration, reporting and accountability are in accordance with Permendagri Number 20 Year 2018 concerning Village Financial Management. (2) Implementation of Good Governance principles in the management of APB Nagari on the nagari of Koto Nan Tigo Utara Surantih and Koto Nan Tigo Selatan Surantih has been carried out quite well by Nagari government